PREVENTION PROGRAM FOR PEOPLE LIVING WITH TYPE 2 DIABETES MELLITUS : A SYSTEMATIC REVIEW - Akub Selvia; Wahyu Gito Putro; Zaki Maulana Riski; Ninda Roudlotul Janah; Annisa Sabilia Andini; Agus Dwi Pranata (Journal Keperawatan, 2023)
Noncommunicable diseases (NCDs) are diseases caused by a mix of genetic, physiological, environmental, and behavioral factors. The prevalence of NCDs is comparable to that of Diabetes Mellitus (DM) and hypertension. Diabetes Mellitus cases were 476 million worldwide in 2019, with 578 million anticipated in 2030 and 700 million predicted in 2045. This is a Systematic Review study that employs the "Preferred Reporting Items for Systematic Review and Meta-Analysis Guideline" and is presented as "Synthesis without Meta-Analysis."All studies chosen for review were found in internet resources such as PubMed, ScienceDirect, and Emeral Insight. All research examined ranged from 2013 to 2023. The keywords used to search the examined studies were "Programme", "Type 2 Diabetes Mellitus", and "Prevention". Furthermore, the articles chosen all used a cohort research design. The findings of the research were undertaken to determine the most effective T2DM program, particularly preventive measures. The present PROLANIS initiative in Indonesia needs to be strengthened by improving interactions with stakeholders.